Volcanic hazards, risks and disasters (Hazards and disasters series (Elsevier), 2015)
Volcanic Hazards, Risks, and Disasters provides you with the latest scientific developments in volcano and volcanic research, including causality, impacts, preparedness, risk analysis, planning, response, recovery, and the economics of loss and remediation. It takes a geoscientific approach to the topic while integrating the social and economic issues related to volcanoes and volcanic hazards and disasters. Throughout the book case studies are presented of historically relevant volcanic and seismic hazards and disasters as well as recent catastrophes, such as Chile's Puyehue volcano eruption in June 2011.